Educação Financeira: uma proposta de ensino com alunos do ensino médio - Rodrigues, Murilo Augusto (2024)
This study evaluated the implementation of a sequence of activities on financial education. The aim was to investigate the importance of structured financial education within the High School curriculum, in accordance with Brazilian educational guidelines such as the Law of Guidelines and Bases of National Education (LDB), the National Common Curricular Base (BNCC), and the Paulista Curriculum. The research sought to analyze how financial education, integrated with practical experiences and active methodologies, contributes to the development of significant financial competencies for the students, preparing them to make informed and conscious financial decisions. The study was conducted at a State School of the Integral Education Program, located in São Miguel Arcanjo, São Paulo, with a class of 25 students, 17 of whom participated in the research. Based on the theories of Freire, Ausubel, Vygotsky, and Kolb, which advocate for education as a process of emancipation, critical reflection, and contextualization, the research integrated financial education into the curriculum as an elective subject. Active methodologies such as flipped classroom, gamification, and simulations were used to promote engaged and meaningful learning. These strategies allowed students to apply theoretical knowledge in practical situations, such as simulating a bank agency, resulting in increased engagement and understanding of financial concepts. Data collection occurred over 11 sessions, each lasting 90 minutes, recorded through logbooks where students expressed their perceptions and interactions with the activities. Data analysis, through categorization, revealed recurring themes such as the importance of a personalized approach to financial education, adjusted to the socioeconomic profile of students. The research was divided into two stages: the first, exploratory, analyzed students' prior knowledge to identify their initial perceptions and starting points, ensuring that teaching was aligned with their realities. The second stage aimed to broaden students' horizons through awareness-raising education in the proposed activities, empowering them to use education as a means to achieve social advancement. The results indicated that the combination of active and reflective methodologies, coupled with a Freirean approach, promoted the development of financial competencies and critical thinking in students. Practical activities, such as field trips and financial simulations, were highly valued by the students. The integration of the school community in activities, such as simulating bank service, reinforced the practical importance of financial knowledge and contributed to meaningful learning. In conclusion, the study demonstrated that financial education should be considered an essential component of the school curriculum, playing a fundamental role in the comprehensive development of students. The inclusion of this content goes beyond technical training, contributing to the development of socio-emotional competencies and preparing young people to face financial challenges in an informed and responsible manner. The elective "The Building of Your Dream Starts Here!" proved to be effective in empowering students, providing them with tools to become agents of change in their communities and contribute to a fairer society.